Process and Labour Utilization in The Electronic Industry: A Simulation Approach - Omar, M.Khaled; Abdullah, Rohana; Abd. Rahman, Md. Nizam (2012)
Process utilisation that ensures all workstations are balanced is essential factor for factory productivity. Another important factor that has to be considered is the Man-to-Machine (M-to-M) ratio which provides an answer to how much manpower should be assigned to a machine. This paper reports on a simulation approach that aims to simultaneously provide a solution to the problems of process and M-to-M ratio utilisation. The results of the simulation provide an accurate picture for the system understudy in terms of the bottleneck process, optimal utilisation and M-to-M ratio.